The emerging roles of managers in influencing life insurance agents to perform customer-orientation behaviour - Mohd Noor, Nor Azila; Muhamad, Azli (Penerbit Universiti Utara Malaysia, 2008)
The issue of salespeople's customer-orientation behaviour has attracted the interest of both academic and business people. One major factor which has been increasingly discussed as a determining factor of salespeople's customerorientation behaviour is role perception, which consists of role ambiguity and role conflict. In this study, the influence of these two factors on salespeople S customer-orientation behaviour was examined. Data gathered from 445 life insurance agents were used to test the hypothesised relationships. The results supported the hypotheses that both rule ambiguity and role conflict negatively affect salespeople to adopt customer-orientation behaviuur in their selling activities. The theoretical implications and managerial implications, particularly the important role of insurance managers in dealing with insurance agent's customer-orientation behaviour, of these findings are discussed.